Dampak Regulasi Syariah Terhadap Perkembangan Ekonomi di Negara Islam: Studi Komparatif - Aini, Fauqah Nuri; S, Syahpawi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the impact of Sharia regulations on the development of Islamic economics in several Muslim countries, namely Indonesia, Malaysia, Saudi Arabia, and Turkey. The research employs a mixed-methods approach, combining quantitative analysis using multiple linear regression with qualitative analysis through document review and in-depth interviews. The results indicate that countries with structured, harmonized, and consistent Sharia regulatory frameworks tend to experience more significant growth in their Islamic economic sectors compared to those facing fragmented regulations. Malaysia and Saudi Arabia have established robust regulatory systems, which positively influence the growth of Islamic financial assets and increase the contribution of the Islamic sector to national GDP. Conversely, Indonesia and Turkey face challenges in regulatory harmonization, which has led to a slower development of their Islamic economies. These findings highlight the importance of institutional collaboration and regulatory adaptation to global market dynamics in order to build a more competitive and sustainable Islamic economic ecosystem.